Specyfika rosyjskiego autorytaryzmu - Bartnicki, Adam Robert (Wydział Nauk Politycznych i Dziennikarstwa UAM w Poznaniu, 2011)
One of the significant theoretical issues in political science involves the accurate definition of the political regime in modern Russia, the description of its mechanisms, and outlining its specific nature and developmental perspectives. At present, these matters are somewhat chaotic for two reasons. Firstly, researchers are cautious in applying equivocal notions to a system which is both ambiguous and highly dynamic, and consequently changeable. Secondly, there is a multitude of research constructs seeking a new definition, or at least a new conception, in order to describe the reality of transforming Russia.
The Specificity of Russian Authoritarianism